Capital Markets Development : A Primer for Policymakers - World Bank Group (World Bank, Washington, DC, 2021)
The COVID-19 pandemic adds further challenges to the development of capital markets. For many emerging markets and developing economies challenges have intensified because of (i) the deterioration in the macroeconomic environment, including the contraction of the economies, and larger fiscal deficits, (ii) reduced investor appetite due to uncertainty, and (iii) the nature and scale of the interventions used by governments to support the economy which, while necessary, might have limited the viability of different capital markets solutions, at least in the short to medium term. That said, this does not alter the fundamental premise that it is important to develop alternative finance mechanisms for key strategic sectors. Rather, if anything, the need for capital markets solutions is more critical than ever given the much more limited space that governments, and potentially also banks, will have going forward to support new financing. This Primer will be followed by a series of practitioner papers. As part of its knowledge management agenda, the WBG is working towards deepening the understanding of the use of capital markets to finance strategic sectors, from corporate to infrastructure, housing, SME, and climate change financing. Along these lines, reports will be prepared, as appropriate, to help practitioners identify the key challenges that could prevent the mobilization of capital markets financing to these strategic sectors as well as key actions to address them.